Separation Benzene and Toluene from BTX using Zeolite 13X - Abdul-Karim Mohammed, Abdul-Halim; Kadir Baki, Mohand (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
This work deals with the separation of benzene and toluene from a BTX fraction. The separation was carried out using adsorption by molecular sieve zeolite 13X in a fixed bed. The concentration of benzene and toluene in the influent streams was measured using gas chromatography. The effect of flow rate in the range 0.77 – 2.0 cm3/min on the benzene and toluene extraction from BTX fraction was studied. The flow rate increasing decreases the breakthrough and saturation times. The effect of bed height in the range 31.6 – 63.3 cm on benzene and toluene adsorption from BTX fraction was studied. The increase of bed height increasing increases the break point values. The effect of the concentration of benzene in the range 0.0559 – 0.2625g/cm3 and toluene in the range 0.144 – 0.21 g/cm3 was studied. The increasing of inlet solute concentration increases the slope of the breakthrough curve. The amount of toluene adsorbed in the packed bed at any time is higher than that of benzene while it decreases after the saturation time. The best operating conditions in this work for benzene and toluene adsorption are 0.77 cm3/min of feed and 31.6 cm bed height of zeolite 13X.